Interdisciplinary team care as a strategy for prioritizing the health of the elderly (Research, Society and Development, 2023)
The aim of the article was to learn about the interdisciplinary team's care for the elderly by monitoring the activities of the elderly in community centers in the North, Northeast and South regions. Community Center of the Northeast region of Brazil. Geriatric Center of the Southern Region of Brazil. These institutions are of paramount importance for improving the quality of life of the elderly, with a view to monitoring the activities carried out, seeking to identify in the elderly population their perception of participation in social groups, and the improvements obtained with the activities carried out. The methodology emphasizes a qualitative and quantitative study, through a qualitative, descriptive survey with cross-sectional samples, from these data literary studies were collected, with the analysis of secondary data regarding the use of content in an ethical and professional way towards the elderly. It is worth highlighting the coexistence groups as a support for improving the quality of life of the elderly, since they promote participation, through various activities, which makes one reflect on the aging process, the quality of life and the appreciation of life itself . The activities developed by the Living Centers are of paramount importance for the elderly. Because, with these practices developed, they have a better quality of life, they manage to make new friendships that are also fundamental, and they no longer feel useless, in addition to developing their autonomy and self-esteem, automatically becoming happier.